PENERAPAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL MENGGUNAKAN ALAT PERAGA PADA MATERI PELAJARAN PAI DI SMP NEGERI 35 SINJAI - Suriyati, Suriyati; Mytra, Prima; Jaya Nur, Makmur; Wahdania, Wahdania (Universitas Islam Ahmad Dahlan (UIAD), 2024)
Learning facilities are an important aspect in the educational process, where educators use various media as tools to convey material so that students can understand it more effectively. The aim of this research is to evaluate the application of audio-visual based learning media using teaching aids in Islamic Religious Education material at SMP Negeri 35 Sinjai. The research method used is qualitative, with the researcher as the main instrument and using interviews as a data collection technique. This research also includes collecting information regarding the experiences of class VIII junior high school students regarding the application of audiovisual media. The research results show that the development of information technology has a positive impact on the education sector, where media plays a crucial role in the learning process. The use of learning tools by teachers as communication tools during learning helps students understand the material better. The use of teaching aids also makes a major contribution to the teacher's ability to develop teaching materials, encourage creativity and innovation in the teaching process.